Factors influencing intensive care admission: a mixed methods study of EM and ICU. (February 2017) - Emerson, Philip; Brooks, Daniel; Quasim, Tara; Puxty, Alex; Kinsella, John; Lowe, David J.
Abstract : Objectives: Twenty-six percent of ICU patients in the UK are referred directly from the Emergency Department (ED). There is limited literature examining the attitudes or practice of ED/ICU physicians towards referrals from the ED to the ICU. We examined these attitudes through a mixed methods study, designing a model incorporating these attitudes to promote a shared mental model between ED and ICU specialities. Methods: Individual semistructured interviews were conducted with 11 ED consultants and 11 ICU consultants at two hospitals in the west of Scotland. Interviews were based on 10 'case-based vignettes' representing patients for whom referral from the ED to the ICU is borderline or challenging. Participants were asked to note whether they would refer/accept the patient from the ED to the ICU. The proportions of participants from each speciality choosing to refer or accept patients were compared using a t -test comparing proportions. The reasons behind these decisions were explored during the semistructured interviews. Results: Twelve factors emerged as influencing the decisions made by the participants. These belonged three core themes: patient factors, clinician factors and resource factors, which were incorporated into a shared mental model. Two cases demonstrated statistically significant differences in referral rates between specialities. There were also clinically significant differences among other cases. Conclusion: We have described the attitudes of physicians towards ED to ICU referrals in two west of Scotland hospitals, and we have demonstrated that there is a difference in the aspects of the decision-making process. We have developed a model encompassing all factors considered by participants when assessing these difficult referrals. It is hoped that this model will promote shared and more efficient decision-making in the future.